Real-time analysis of gut flora in Entamoeba histolytica infected patients of Northern India - Verma, Anil Kumar (BioMed Central, 2012)
BACKGROUND: Amebic dysentery is caused by the protozoan parasite Entamoeba histolytica and the ingestion of quadrinucleate cyst of E. histolytica from fecally contaminated food or water initiates infection. Excystation occurs in the lumen of small intestine, where motile and potentially invasive trophozoites germinate from cysts. The ability of trophozoites to interact and digest gut bacteria is apparently important for multiplication of the parasite and its pathogenicity; however the contribution of resident bacterial flora is not well understood. We quantified the population of Bacteroides, Bifidobacterium, Ruminococcus, Lactobacillus, Clostridium leptum subgroup, Clostridium coccoides subgroup, Eubacterium, Campylobacter, Methanobrevibacter smithii and Sulphur reducing bacteria using genus specific primers in healthy (N = 22) vs amebic patients (E. histolytica positive, N = 17) stool samples by Real-time PCR. RESULTS: Absolute quantification of Bacteroides (p = .001), Closrtridium coccoides subgroup (p = 0.002), Clostridium leptum subgroup (p = 0.0001), Lactobacillus (p = 0.037), Campylobacter (p = 0.0014) and Eubacterium (p = 0.038) show significant drop in their population however, significant increase in Bifdobacterium (p = 0.009) was observed where as the population of Ruminococcus (p = 0.33) remained unaltered in healthy vs amebic patients (E. histolytica positive). We also report high prevalence of nimE gene in stool samples of both healthy volunteers and amebic patients. No significant decrease in nimE gene copy number was observed before and after the treatment with antiamebic drug. CONCLUSIONS: Our results show significant alteration in predominant gut bacteria in E. histolytica infected individuals. The frequent episodes of intestinal amoebic dysentery thus result in depletion of few predominant genera in gut that may lead to poor digestion and absorption of food in intestine. It further disturbs the homeostasis between gut epithelium and bacterial flora. The decrease in beneficial bacterial population gives way to dysbiosis of gut bacteria which may contribute to final outcome of the disease. Increase in the copy number of nimE gene harboring bacteria in our population reflects possible decrease in the availability of metronidazole drug during treatment of amoebiasis.